2017
DOI: 10.1108/ijhcqa-06-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Reducing wrong intraocular lens implants in cataract surgery

Abstract: Purpose Wrong lens implants have been associated with the highest frequency of medical errors in cataract surgery. The purpose of this paper is to explore the use of the Systems Engineering Initiative for Patient Safety (SEIPS) framework to sustainably reduce wrong intraocular lens (IOL) implants in cataract surgery. Design/methodology/approach In this mixed-methods study, the SEIPS framework was used to analyse a series of (near) misses of IOL implants in a national tertiary specialty hospital in Singapore. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Eight articles defined or described near misses as situations where events had not reached the patients 30,32,33,35–39 . Ten articles defined or described near misses that included events that had reached patients 31,34,40–45 and could be considered to potentially cause harm 46,47 . Early et al 48 described learning from a “near-miss sentinel event,” but provided no further information about the event or its impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight articles defined or described near misses as situations where events had not reached the patients 30,32,33,35–39 . Ten articles defined or described near misses that included events that had reached patients 31,34,40–45 and could be considered to potentially cause harm 46,47 . Early et al 48 described learning from a “near-miss sentinel event,” but provided no further information about the event or its impact.…”
Section: Resultsmentioning
confidence: 99%
“…Where there was evaluation, articles commonly measured the occurrence of safety events as a metric for impact. Reductions were seen in unintended event rates, commonly the near misses themselves 30,33,35–41,43–47 . Loh et al, 47 for example, described a reduction in the number of intraocular lens events (near misses) from 5.89 before to 3.55 per 1000 cases.…”
Section: Resultsmentioning
confidence: 99%
“…In a literature review by researchers from England it is demonstrated that 1 out of each 20 surgical patients experienced an undesirable and avoidable event during care, a fact that reinforces the need to improve all processes involving surgical care (7) . With regard to ophthalmic surgeries, among the possible adverse events are visual deficiencies and loss of vision, to, making feasibal an environment with effective and stable communication is a way to minimize occurrences of errors, making surgical processes safer (8) . Thus, the importance of investing in planning and appropriate management of materials used in ophthalmic surgeries is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show communication problems are root causes of wrong IOL implants in cataract surgery [26]. In New York State, wrong implant-related errors account for 63 percent of the total number of malpractice claims and data from Veterans Health…”
Section: Comparison With Prior Workmentioning
confidence: 99%